PENGARUH FOMO (FEAR OF MISSING OUT) DAN INFLUENCER TERHADAP NIATAN UNTUK MEMBELI PADA E-COMMERCE - Radianto, Amelia Josefien Viotty; Kilay, Trisye Natalia (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine whether there is an influence of FoMO, influencer on intention to buy. The data collection method is through distributing questionnaires to generation Z born from 1996 to 2015 who use social media in Ambon. The sampling technique uses the accidental sampling method. The data analysis method uses multiple linear regression analysis using SPSS statistical tools. The results of this research provide empirical evidence that only influencers have a positive influence on Gen Z's intention to buy on e-commerce in Ambon City. This research failed to find any influence of FoMO on Gen Z's intention to buy from e-commerce in Ambon City.